ANALISIS PENGARUH DAYA TARIK EKOWISATA TERHADAP MINAT BERKUNJUNG WISATAWAN DI KETAPANG URBAN AQUACULTURE MAUK, KABUPATEN TANGERANG - Ariesta, Irma; Sarudin, Rendy (LPPM Institut Pendidikan Nusantara Global, 2023)
The aim of this research is to find out several problems related to the lack of interest in visiting tourists at Ketapang Urban Aquaculture. This research is quantitative research where researchers use research instruments to collect data. The results of the instrument were then analyzed using the SPSS application.The results of this study can be interpreted that: (1) Ecotourism Attraction has a positive and significant influence on Interest in Visiting Ketapang Urban Aquaculture Mauk as evidenced by the results of the T test of 16,329. (2) From simple linear regression Y = 4.498 + 0.564X. (3) In terms of R Square, it is 73.1% and has an influence on the variable of interest in visiting. While the remaining 26.9% is influenced by other variables not examined.